Book Review: Pink, D.H. (2009). Drive: The Surprising Truth about What Motivates Us - Kathleen Fite (Networks: An Online Journal for Teacher Research, 2010)
This three-part, six-chapter book has taught me, an educator, more about motivation than any other resource I have used in the past. Part One encourages us to think beyond our rewardand-punishment system to a new way of thinking about motivation. Part Two presents what he refers to as Type I, “intrinsic behavior where we have an innate need to direct our lives and how we learn; and, how this type of behavior enhances performance and satisfaction.” Part Three, referred to as the Type I Toolkit, provides a variety of resources designed to support Type I behavior. Pink makes connections to business as well as schools. It is these latter connections that educators and administrators should closely examine as I think they offer promise for 21st century school improvement.